INTERSECTIONALITY AND EQUITY IN EDTECH: A CRITICAL ANALYSIS OF LEARNING APPS IN MARGINALIZED COMMUNITIES - Loso Judijanto; Sofia F Rahmani; Rinda Riztya (Adisam Publisher, 2025)
Abstract This research aims to critically analyze how digital learning applications facilitate or widen educational disparities in marginalized communities through an intersectional and equity approach. In the context of the rapid advancement of educational technology (EdTech), it is crucial to understand how social identity factors such as gender, race, economic status, disability, and geographic location interact and influence access to and the quality of learning experiences. This study uses a desk study method by examining recent academic literature, policy reports, and evaluation results of learning applications used in various marginalized communities. The analysis shows that most learning applications still do not fully consider the needs of diverse users, especially those at the intersection of multiple forms of vulnerability. The lack of representation, uniform design approaches, and limited digital infrastructure exacerbate existing digital exclusion. This research recommends the development of more inclusive, equity- and intersectional-based learning applications that involve community participation in the design and evaluation process. In this way, EdTech can contribute more equitably to improving the quality of education in marginalized communities.